2018
DOI: 10.1371/journal.pone.0198673
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin selectively transported to cerebrospinal fluid from blood under hypoxic/ischemic conditions

Abstract: AimThe aim of this study was to determine and to verify the correlation between the amount of prolactin (PRL) levels in the blood and in the cerebrospinal fluid (CSF) by various causes of death as an indicator for acute hypoxia in autopsy cases. It is to confirm the cause of the change in prolactin level in CSF by in vitro system.Materials and methodsIn autopsy materials, the PRL levels in blood from the right heart ventricle and in the CSF were measured by chemiluminescent enzyme immunoassay, and changes in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 45 publications
2
16
0
Order By: Relevance
“…Subsequently, the filter was placed upright in the culture medium. Schroten H, (2016) established this method in a choroid plexus model [68][69][70][71][72], and we previously described this method in a report on the physiologic significance of the blood-cerebrospinal fluid barrier and prolactin [73].…”
Section: Cell Culture Modelsmentioning
confidence: 99%
“…Subsequently, the filter was placed upright in the culture medium. Schroten H, (2016) established this method in a choroid plexus model [68][69][70][71][72], and we previously described this method in a report on the physiologic significance of the blood-cerebrospinal fluid barrier and prolactin [73].…”
Section: Cell Culture Modelsmentioning
confidence: 99%
“…Conversely, after 30 min of culture, the T3, T4, and Tg levels under hypoxic conditions were lower than those under normoxic conditions. Furthermore, the levels of VEGF, which is a marker of cell function under hypoxic conditions [39], were measured, and no decreases were observed, suggesting no thyroid cell dysfunction. Secretion of the thyroid hormone decreased under hypoxic conditions compared to normoxic conditions after 30 min of culture, suggesting that this could be a result of long-term hypoxia and decreased cell function.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study reported that PRL selectively transported to CSF from blood under hypoxic/ischemic conditions. 16 Methamphetamine reportedly alters the dopaminergic system and damages the blood-brain barrier (BBB), the structure that protects brain tissue from substances circulating in the blood. 32 A previous study investigated intermittent hypoxia on DA release in rat brain treated with amphetamine.…”
Section: Discussionmentioning
confidence: 99%